1974
DOI: 10.1111/j.1365-2842.1974.tb00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between facial morphology and activity of the masticatory muscles

Abstract: Summary The relation between muscle activity and facial morphology was studied in twenty‐five boys and twenty‐seven girls, aged 9–11 years. The activity in the anterior and posterior parts of the temporal muscle, the masseter muscle and the upper lip was recorded bilaterally with the mandible in postural position and during chewing, swallowing and maximal bite. The electromyograms were analysed in respect of maximal mean voltage amplitude and the duration of muscle activity. Facial morphology was studied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
114
6
8

Year Published

1976
1976
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(140 citation statements)
references
References 17 publications
12
114
6
8
Order By: Relevance
“…Finally, the molars reach a balanced position (Masumoto et al, 2001). The lower molars are close to the attachment area of the masseter (Ingervall and Thilander, 1974;Tabe, 1976), and therefore are more influenced by the force of the masseter. Subjects with horizontal growth pattern have a stronger masseter (Ingervall and Helkimo, 1978), and it is not surprised that the molars of patients with the horizontal growth pattern have a greater buccal inclination compared to the molars of those with the vertical growth pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the molars reach a balanced position (Masumoto et al, 2001). The lower molars are close to the attachment area of the masseter (Ingervall and Thilander, 1974;Tabe, 1976), and therefore are more influenced by the force of the masseter. Subjects with horizontal growth pattern have a stronger masseter (Ingervall and Helkimo, 1978), and it is not surprised that the molars of patients with the horizontal growth pattern have a greater buccal inclination compared to the molars of those with the vertical growth pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the tooth-alveolar bone complex is an important factor in orthodontic treatment planning, assessment of treatment progress, and the determination of treatment outcomes (Aasen and Espeland, 2005). The structure of the tooth-alveolar bone complex changes following alterations in loading by forces developed through the dentition and joint as the muscles contract during function (Ingervall and Thilander, 1974;Dechow and Hylander, 2000). Various growth patterns have different biting forces and biological adaptations, and therefore, result in different mandibular toothalveolar structures (Dechow and Hylander, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…17 EMG evaluations of masticatory muscles have produced divergent results when individuals with different vertical facial growth are compared. Some authors have observed that the amplitude of EMG values in temporal 1,2,6 and masseter 1,3,6 muscles is always greater in short-faced individuals. Some articles reported that the longer the face of an individual, the greater the EMG activity of the temporal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Their function and anatomy have been evaluated by electromyographic (EMG) exams, [1][2][3][4][5][6][7][8][9] bite force, 10 computed tomography of muscle thickness, 11 ultrasonography 5,[12][13][14][15] and magnetic resonance, 16 in addition to immunohistochemistry evaluations of muscular fibers. 17 EMG evaluations of masticatory muscles have produced divergent results when individuals with different vertical facial growth are compared.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear however that bread was the staple food of many and that the grain from which it was made varied from place to place. 13 A possible relationship between facial growth and muscle size or activity has been suggested by several studies using human subjects [14][15][16][17][18][19][20] and the hypothesis that jaw size may be affected adversely by reduced mastication has been supported by the results of animal experiments. 21,22 Others have cast doubt on the muscle-exercise theory, considering that normal jaw growth would proceed over a wide range of activity and that only an altogether exceptional degree of lack of use might affect it.…”
Section: Introductionmentioning
confidence: 99%